Analisis Peran Otoritas Jasa Keuangan Dalam Melakukan Penanggulangan Terhadap Investasi Ilegal di Indonesia - Reza Nur Hidayah; Panca Safira Amelia; Endang Kartini Panggiarti (Public Service and Governance Journal, 2023)
This study aims to comprehend the methods used by Indonesia's Financial Services Authority to tackle illegal investments. This is due to the substantial quantity of illegal investments in Indonesia, which can have detrimental impacts on many parties, especially individuals who make these investments. This research employs a normative legal research methodology that takes a statutory approach. The primary and secondary legal materials used are primary legal materials in the form of laws and regulations, including those pertaining to the Supervision of the Financial Services Authority against Illegal Investments (UU No. 21 of 2011), and investment-related books and journals, including illegal and OJK investments. The study's findings demonstrate that the Financial Services Authority, as required by Law No. 21 of 2011 concerning the Financial Services Authority, has the authority to protect the public's legal rights through public education campaigns, provision of facilities for customer complaints, and handling of illegal investments through the revocation of business licenses or payment. and presented a court case. An Investment Alert Task Force, which was established by the Financial Services Authority, was tasked with monitoring investments in general and illegal investments in particular.